Milking Insights: An Ethnographic Examination of Fairlife's Instagram Content - Karissa Palmer; Julysa A. Benitez; Logan Baker; Holli Leggette; Emily Fuller (Journal of Applied Communications, 2025)
The dairy industry is currently facing challenges in meeting the ongoing needs of a growing population while meeting the increased demands for dairy products, which have resulted from the growing demand for protein-based dairy products. Simultaneously, the dairy industry faces several challenges in improving consumer perceptions of dairy production as they gather much of their information about the dairy industry, including crisis information, from mass media and social media sources. Therefore, we sought to use a short-term ethnographic approach to explore the content presented on @fairlife’s Instagram, including categories of products promoted; emerging themes of content presented; consumer interactions and engagement; and @fairlife’s presentation during and after the Fair Oak’s crisis (a major animal welfare scandal). We analyzed 732 posts posted on the Instagram account between January 25, 2014, and March 6, 2024, with 161 being videos or reels, 506 single photos, and 65 carousels. We found 45,750 comments and 206,510 likes among the 732 posts with a total response (engagement: likes and comments) of 253,260. We found that 2% ultra-filtered milk is presented the most on @fairlife’s Instagram profile. We identified 12 emerging themes with the most prominent being seasonal or holiday related. Most comments included positive words with Fairlife being the most frequently used word. Consumers were initially disappointed in Fairlife after the crisis, but consumer sentiment eventually shifted, which could have been the result of the company’s strategic crisis communication efforts. Additionally, we found that @fairlife maintains its audience interest beyond product promotions.
Keywords: milk; ethnography; Instagram; self-presentation; crisis communication